PEMIKIRAN AS-SUYUTHI DALAM BIDANG FIQH SYAFI’I TELAAH KITAB AL-ASYBAH WA AL-NAZHAIR - Nurotun Mumtahanah (Universitas Islam Lamongan, 2019)
In the discourse of the Al-Syafi'I school of thought there is a monumental book talking about the principles of fiqhiyyah, namely Al-Asybah Wa Al-Nazhair Fi Qawaida Wa Furu'i Fiqhi Al-Syafi'iyyah by Abdurrahman bin Abu Bakar Al-Suyuthi (D. 911 H). The writing of Al-Asybah Wa Al-Nazhair is proof of the al-Suyuthi's skills in the field of fiqh and fiqhiyyah rules. Therefore, It needs to be studied further, in the context of more exploration and scientific development. For this reason, this study will focus on the background and the content of the Al-Asybah Wa Al-Nazhair with all the advantages and characteristics. In this study, it was found that the Al-Asybah Wa Al-Nazhair Fi Qawaida Wa Furu'i Fiqhi Al-Syafi'iyyah by Abdurrahman bin Abu Bakar Al-Suyuthi (W. 911 H) was written systematically in seven chapters, namely; 1). Five methods of jurisprudence that are often used as references in the subject of fiqh; 2). General methods used in dealing with partial problems; 3). The methods that are contrary to one another, without privileging one of the parties / opinions because it occurs in the scope of furu'iyah (not the principle problems); 4). The legal problems that are well known and widely heard and reprimands for fiqh experts who don't know it; 5). Some reviews in the (fiqh) chapter; 6). The chapter about syubhat and relating to it; 7). Some views about: a). Doing something that contains two contradictions; b). Doing something outside of time (specified); c). Some problems (mentioned in the syarh al- muhadzzab); d). (thirty) problems for which there is no reason not to know and has been arranged (by al-Suyuthi) into a nazhm (poetry).